mpact of ice conditions to the navigation in the Novaya Zemlya and Spitsbergen region in XVI–XVII centuries - V. L. Derzhavin (Лëд и снег, 2015)
In the 16th–17th centuries, West European navigators made numerous but mostly unsuccessful efforts to open a new way, i.e. the North-East Passage, to China and India. Among three possible routes of that time the basic one ran through straits of the Vaigach Island but it was almost impassable due to heavy ice situation. At the same time Russian merchants regularly went on their ships from Pomorie to Siberian river mouths, and in the opposite direction, though they did also meet complicated ice situations. Russian navigator and geographer F.P. Litke (1797–1882) noticed that the ice situation in one or another region of the Barents Sea seriously changed from year to year. Russian navigation started in the Russian Pomorie (littoral region of the Russian Arctic) not earlier than at end of June – beginning of July but Europeans knew nothing about this. Because of this, their ships came to the Vaigach region either earlier or later of the time when it was possible to go through the straits. Most often, they came here in the first half- and mid-August. Thus, western sailors could not get this quite narrow navigation «window» of pomors (Russian navigators). And if sometimes (rather rarely) they could catch the right time and go through the strait Yugorski Shar they met extremely heavy ice situation in the Kara Sea. Perhaps for this reason, almost all European expeditions of that time failed.